Kepemimpinan Politik Kalangan Minoritas Agama : Kajian terhadap Tafsir Al-Azhar dan Tafsir Al-Misbah tentang Presiden Non-Muslim - Syamsul Arifin; Muhammad Wahyudi; Muh. Mustakim (Al-Ulum, 2021)
This article focuses on the study of non-Muslim leadership, which is mentioned in several verses in the Qur'an and often triggers debates in the public sphere, especially at the moment of electoral politics in Indonesia. Because the discussion about this often uses verses from the Qur'an as justification, it is interesting to examine the views of the commentators in Indonesia, which is focused on Surah Al-Maidah verse 51. To explore the views of the two commentators, this study uses library research by comparing (comparative analysis) between Tafsir Al-Azhar and Tafsir Al-Misbah. The study of the opinions of the two commentators finds out that the political positions of non-Muslims as leaders for Muslims have two different views. First, not. Second, the prohibition is to make non-Muslims as auliya' then Shihab explains the position of non-Muslims in three parts, one of which is that a non-Muslim who lives in peace with Muslims has the same rights and obligations as Muslims, as well as the right to be a leader.